Pengaruh Struktur Modal, Kepemilikan, dan Faktor Eksternal pada Penentuan Nilai Perusahaan - Suteja, Jaja; Manihuruk, Winston (Jurnal Trikonomika, 2009)
This Study investigates the factors which influence value of the firm in publicly traded companies listed at Jakarta Stock Exchange. In this research, capital structure influenced by liquidity ratio, operational income volatility, profitability, size of the firm, capital expenditures, economy crisis and exchang rate. Meanwhile, value of the firm be influenced by capital structure estimate, managerial ownership, institutional ownership, profitability, economy crisis, exchange rate and IHSG. The result of this research will be expected to explain determinants of capital structure and value of the firm thereby the firm could anticipate its in order to avoid over leverage and decreaing value of the firm. This research using survei method toward publicly traded company listed in Indonesian Stock Exchange as grouped in manufacturing companies from 1994to 2005. The data collected consist of daily transaction share and lHSG from 1994 to 2004. This research using panel data analysis. According to the result of this research could be formulate concluding remark these: value of the firm influenced by capital structure, managerial ownership, institutional ownership, economic crisis, exchange rate and IHSG. Meanwhile capital structure influence liquidity ratio, earning volatility, profitability, size of the firm, capital expenditures, economic crisis and exchange rate.